MENINGKATKAN KOMPETENSI SISTEM PEMERINTAHAN DESA DENGAN STRATEGI MODEL INKUIRI BERBASIS MANUSIA SUMBER BELAJAR - Karmini, Sri (Universitas Pendidikan Indonesia, 2016)
The formulation to the problem this research is how the learning process, how big increase student learning outcomes in the competence of the village administration system, as well as changes in the behavior of students after using a strategy based human inquiry model of learning resources in the fourth-grade elementary school Keputran 06â€™s Classroom Action Research. This is done by two cycles. The results from this research that there is a change of behavior of learners towards the positive aspects of cooperation, liveliness, honesty, self-confidence. The average student learning outcomes have increased from the first cycle to cycle 2 at an average of 71.60 with the first cycle of students who achieve minimum completeness criteria.as much as 70% while the average of 87.50 with a second cycle student who achieve 88% minimum completeness criteria. Thus an increase in the thoroughness of the first cycle to the second cycle by 18%.Keywords:Â learning modelÂ constructivism, two dimension media and three dimensions.